Regulation of Land Lease Rights Period for Foreign Citizens in Indonesia - Putu Rosa Paramitha Dewi; I Nyoman Budiana (Jurnal Hukum Prasada, 2021)
Many foreigners have come and lived in Indonesia. This results in the increasing need for land and buildings for foreigners to be used as a residence. Foreigners are not allowed to have ownership rights over land in Indonesia, however, in this case, the law provides rights for foreigners to own land in Indonesia, but limited to Right of Use and Leaseholds for Buildings. This absence of UUPA has the potential to lead to smuggling of laws, because the lease period granted to foreign citizens is not limited so that foreign citizens can stay in Indonesia for a very long. If the land is fully controlled by foreign citizens or for a long period of time, it is feared that the people's welfare will decrease in the management of the land. Therefore, this study aims to analyze the legal of land right for foreign citizens in Indonesia and the regulation of the period of land lease right for foreign citizens in Indonesia. The type of research used is a normative juridical research through a statutory approach, a case approach, and a conceptual approach. A foreign legal entity wishing to have Building Use Rights (HGB) must fulfill two elements, namely that it is established according to Indonesian law and domiciled in Indonesia, must exist. Besides that, regulation for the period of land lease rights for foreigners have not been regulated in land-related regulations in Indonesia so that there is a vacuum of norms.